Collaborative Creativity in Remote Work Teams: A Network Analysis of Digital Brainstorming Sessions - Najwa Syarofa; Rami Hariri; Yara Abed (Journal of Loomingulisus ja Innovatsioon, 2025)
The shift to remote work has transformed the way teams engage in creative processes, making digital collaboration tools central to brainstorming and innovation. This study aims to investigate the dynamics of collaborative creativity in remote work settings by analyzing patterns of interaction during digital brainstorming sessions. A mixed-methods network analysis approach was employed, combining social network analysis with qualitative content analysis to map communication structures and creative idea flow across 18 virtual teams composed of 162 participants from diverse professional backgrounds. Data were collected from 54 recorded online brainstorming sessions conducted over a period of three months. Results indicate that teams with more decentralized interaction networks and balanced participation demonstrated higher levels of creative idea generation and convergence. Findings further reveal that the quality of creative outputs is influenced not only by individual contributions but also by the connectivity and diversity of collaborative ties within the team. The study concludes that fostering inclusive and distributed patterns of interaction is key to enhancing creativity in virtual environments.